2009
DOI: 10.1021/la9010289
|View full text |Cite
|
Sign up to set email alerts
|

Packing Patterns of Silica Nanoparticles on Surfaces of Armored Polystyrene Latex Particles

Abstract: Fascinating packing patterns of identical spherical and discotic objects on curved surfaces occur readily in nature and science. Examples include C(60) fullerenes, (1, 2) 13-atom cuboctahedral metal clusters, (3) and S-layer proteins on outer cell membranes. (4) Numerous situations with surface-arranged objects of variable size also exist, such as the lenses on insect eyes, biomineralized shells on coccolithophorids, (5) and solid-stabilized emulsion droplets (6) and bubbles. (7) The influence of size variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 25 publications
2
51
0
Order By: Relevance
“…A quantitative method based on disk centrifugation was developed to monitor the amount of nanoparticles present in the water phase in solids-stabilized emulsion polymerizations of vinyl acetate, methyl methacrylate, and butyl acrylate. The concentration profile of nanoparticles in the water phase as a function of monomer conversion agreed with theoretical models developed for the packing densities in these systems [120]. Noteworthy was that in the case of silica-nanoparticle-stabilized emulsion polymerization of vinyl acetate, the event of late-stage limited coalescence, leading to small armored nonspherical clusters, could be predicted and explained on the basis of the concentration profiles and particle size measurements.…”
Section: Assembly Of Nanoparticles Onto the Surface Of Polymersupporting
confidence: 68%
See 3 more Smart Citations
“…A quantitative method based on disk centrifugation was developed to monitor the amount of nanoparticles present in the water phase in solids-stabilized emulsion polymerizations of vinyl acetate, methyl methacrylate, and butyl acrylate. The concentration profile of nanoparticles in the water phase as a function of monomer conversion agreed with theoretical models developed for the packing densities in these systems [120]. Noteworthy was that in the case of silica-nanoparticle-stabilized emulsion polymerization of vinyl acetate, the event of late-stage limited coalescence, leading to small armored nonspherical clusters, could be predicted and explained on the basis of the concentration profiles and particle size measurements.…”
Section: Assembly Of Nanoparticles Onto the Surface Of Polymersupporting
confidence: 68%
“…Bausch et al [83,84] showed that for large droplets onto which thousands of microspheres were assembled, this rule of 12 defects prevailed in the form of five-and seven-neighbor line defects, or grain boundary scars. Bon and coworkers [85] studied a system of intermediate size (tens to hundreds of particles on a sphere), i.e., the packing patterns of silica nanoparticles on polystyrene latex particles made via Pickering miniemulsion polymerization [86,87]. They found an excellent correlation between the experimental morphology and the nearest-neighbor distribution using metropolis Monte Carlo simulations, using a 12-24 Lennard-Jones potential.…”
Section: Droplets Armored With a Layer Of Adhered Particlesmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a minimum of 12 pentagonal defects must be present for small monodisperse spheres to pack fully around a larger sphere. 71,72 These defects are often described as line defects or grain boundary 'scars' 73 and have been experimentally observed during bright field and fluorescence microscopy studies of water droplets stabilized using polystyrene 74 or silica 72 particles, respectively. A pentagonal defect within a packed monolayer of spheres has an estimated size of 0.70d, which is significantly larger than the fundamental interstitial dimensions of 0.15d.…”
Section: Encapsulation and Release From Colloidosomesmentioning
confidence: 99%